25C‐NBOMe and 25I‐NBOMe metabolite studies in human hepatocytes, in vivo mouse and human urine with high‐resolution mass spectrometry. Issue 5 (12th August 2016) - Wohlfarth, Ariane; Roman, Markus; Andersson, Mikael; Kugelberg, Fredrik C.; Diao, Xingxing; Carlier, Jeremy; Eriksson, Caroline; Wu, Xiongyu; Konradsson, Peter; Josefsson, Martin; Huestis, Marilyn A.; Kronstrand, Robert
Abstract : 25C‐NBOMe and 25I‐NBOMe are potent hallucinogenic drugs that recently emerged as new psychoactive substances. To date, a few metabolism studies were conducted for 25I‐NBOMe, whereas 25C‐NBOMe metabolism data are scarce. Therefore, we investigated the metabolic profile of these compounds in human hepatocytes, an in vivo mouse model and authentic human urine samples from forensic cases. Cryopreserved human hepatocytes were incubated for 3 h with 10 μM 25C‐NBOMe and 25I‐NBOMe; samples were analyzed by liquid chromatography high‐resolution mass spectrometry (LC‐HRMS) on an Accucore C18 column with a Thermo QExactive; data analysis was performed with Compound Discoverer software (Thermo Scientific). Mice were administered 1.0 mg drug/kg body weight intraperitoneally, urine was collected for 24 h and analyzed (with or without hydrolysis) by LC‐HRMS on an Acquity HSS T3 column with an Agilent 6550 QTOF; data were analyzed manually and with WebMetabase software (Molecular Discovery). Human urine samples were analyzed similarly. In vitro and in vivo results matched well. 25C‐NBOMe and 25I‐NBOMe were predominantly metabolized by O‐demethylation, followed by O‐di‐demethylation and hydroxylation. All methoxy groups could be demethylated; hydroxylation preferably occurred at the NBOMe ring. Phase I metabolites were extensively conjugated in human urine with glucuronic acid and sulfate. Based on these data and a comparison with synthesized reference standards for potential metabolites, specific and abundant 25C‐NBOMe urine targets are 5'‐desmethyl 25C‐NBOMe, 25C‐NBOMe and 5‐hydroxy 25C‐NBOMe, and for 25I‐NBOMe 2' and 5'‐desmethyl 25I‐NBOMe and hydroxy 25I‐NBOMe. These data will help clinical and forensic laboratories to develop analytical methods and to interpret results. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We determined the metabolic profile of 25C‐NBOMe and 25I‐NBOMe, two potent synthetic hallucinogens emerged as new psychoactive substances, in human hepatocytes, mice and in authentic human urine samples in order to investigate, which biotransformations occur, and to define suitable analytical targets for forensic analysis